Evaluasi Implementasi Perda Nomer 9 Tahun 2011 Tentang Pajak Air Tanah Kabupaten Blora Pada Tahun 2011-2012 - Angelia D.I.N.; Purwoko .; Supratiwi . (Journal of Politic and Government Studies, 2014)
The title of the background of writing a thesis this is because one of the water sources that is in the earth and can be utilized for everyday needs is ground water. To protect the existence of ground water from the exploitation of water, and to augment pad District Blora and implementation of the water tax.Ground water tax is compulsory contributions to the regions having the character of force based on the law by not rewarded directly and in use for purposes related to the region of the welfare of the people.Tax is impact on a source of income an area.The study is done to know about the evaluation of an implementation of regulation number 9 2011 about the tax ground water District Blora 2011-2012.Methods used in this research using a method of mixed (between a method of qualitative and quantitative methods). An informer in this research is governments Blora dppkad, represented by the head the head of revenue; employees Dppkad, commission, council members b and respondents from society as taxpayers ground water as many as 30 people.The technique is through a questionnaire, collecting data observation that is done with the election of respondents had to use techniques the withdrawal of samples sistimatically, an interview with the technique of snowball, deep as well as by examination of the validity of technical data.The result showed the result of the implementation of perda ground water tax has been good enough.The implementation of this is highly dependent upon the allocation of capital the quality of its human resources, their working bureaucracy, regulations that exist and the role of local government. A factor of impediment to implementation regulations among others: roads, SDM that is still low, natural2resources limited, socialization less, and the imposition of tariffs that is too high.Although realization it can be a bit when compared with the implementation of perda other taxes namum parties dppkad everlastingly increase pad of the ground water every year.Recommendations for the next research the government at regular intervals must do evaluation or polled on the implementation of perda ground water tax in the county of Blora this to the people the government must provide training as well as improve education for officers dppkad implementor, as parties formed dept. of the need for a new, specifically deal with a problem income throughout a county Blora.Keyword : regional regulation, ground water tax, Dppkad District Blora